Aplicación móvil para la gestión de adopción de mascotas en la ciudad de Riobamba mediante el uso del Framework Flutter. - Naranjo Romero, Dayana Estefania (2024)
This research focused on the development of a mobile application for managing pet adoptions in the city of Riobamba, Ecuador. The Flutter Framework was used to explore the potential of this technology to create a digital platform that optimizes adoption procedures. The methodology included a thorough analysis of Flutter and the implementation of best design and development practices specific to this framework. FlutterFlow and Visual Studio Code were used alongside the Kanban methodology to ensure an efficient and structured process. Performance tests were conducted using the FURPS quality model with the help of Firebase Performance Monitoring and Firebase Test Lab. This research revealed important findings, demonstrating that the application shows a 1% faster response time when scaling from 1 to multiple devices. The processing of the home screen decreased by 50%, and there were no frozen frames, ensuring quick interactions without significant delays for users. Efficient resource consumption (CPU and memory) ensured optimal application performance, even on devices with limited hardware capabilities. This study concludes by highlighting the suitability of Flutter for mobile development projects in the field of pet adoption, offering a concrete example of its effective application in this domain. This work has significant implications for future research and improvements in pet adoption management, highlighting Flutter's potential in technological and practical innovation in this field.